Khadicha Sulaymonova – The First Woman Academician Lawyer (Eurasian Research Bulletin, 2023)
This article is devoted to the study of the activities of an outstanding female lawyer, who made a huge contribution to the development of jurisprudence in the days of the Uzbek SSR. When analyzing the biography of Khadicha Sulaimonova, literature in the Uzbek language was studied. Given the lack of information about this figure in Russian, this article can acquaint Russian-speaking readers in detail with the honored worker of science of the Uzbek SSR. Particular attention was paid by the author to strengthening the status of women during the formation of the Uzbek SSR, as well as the development of criminal law on the territory of Uzbekistan